High Wages or Wages For Energy? An Alternative View of The British Case (1645-1700) - José L. Martínez González (European Historical Economics Society (EHES), 2019)
Energy was one of the keys to the remarkable increase in English GDP between 1650 and 1700. Increased per head physical activity and basal metabolic rate led to increased energy consumption. In response, subsistence wages, productivity, wages and incomes increased. Malthusian adjustment explains only 50 per cent of the increase in calorie intake, the other 50 per cent is associated with higher energy consumption. Non-agricultural wages began to differ from agricultural wages. British economic development occurred everywhere, in the city and in the countryside. This approach opens new perspectives to the debate between enclosures and open fields and why underemployment became common among the philosophers' British debates.
Keywords: B11; J30; N13; N33; N53; N73; Q43; Q54; 330; Energy; physical activity; subsistence wages; incomes; wage gap; Malthusian trap; Seventeenth Century; England